2010
DOI: 10.1097/yic.0b013e3283384c74
|View full text |Cite
|
Sign up to set email alerts
|

Age at onset and latency to treatment (duration of untreated illness) in patients with mood and anxiety disorders: a naturalistic study

Abstract: This study was designed to investigate and compare demographic and clinical features with specific emphasis on age at onset, age at first treatment and, in particular, on duration of untreated illness (DUI), in patients with different mood and anxiety disorders. Study sample included 729 outpatients with the following diagnoses: major depressive disorder (n=181), bipolar disorder type I (BD I, n=115) and II (BD II, n=186), generalized anxiety disorder (n=100), panic disorder (n=96), and obsessive-compulsive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
5
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 57 publications
8
70
5
1
Order By: Relevance
“…Finally, studies of anxiety disorders in relation to DUI have recently been reported, showing significant differences in the mean DUI among various conditions (i.e., almost 4 years in patients with panic disorder and more than 8 years in subjects with obsessive-compulsive disorder) [45] as well as peculiar associations with a worse outcome. In particular, a longer DUI was found to be related to a worse response to pharmacological treatment in both obsessive-compulsive disorder [25] and generalized anxiety disorder [24], to more frequent depressive comorbidity in panic disorder [22] and to an earlier age at onset, longer duration of illness and higher rates of comorbidity in generalized anxiety disorder [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, studies of anxiety disorders in relation to DUI have recently been reported, showing significant differences in the mean DUI among various conditions (i.e., almost 4 years in patients with panic disorder and more than 8 years in subjects with obsessive-compulsive disorder) [45] as well as peculiar associations with a worse outcome. In particular, a longer DUI was found to be related to a worse response to pharmacological treatment in both obsessive-compulsive disorder [25] and generalized anxiety disorder [24], to more frequent depressive comorbidity in panic disorder [22] and to an earlier age at onset, longer duration of illness and higher rates of comorbidity in generalized anxiety disorder [24].…”
Section: Resultsmentioning
confidence: 99%
“…However, even though a relationship between anxiety and neurobiological alterations in specific brain areas has been shown [42,43,44], the hypothesis that prolonged latency to treatments correlates with a poor outcome on the basis of cerebral modifications occurring with the progression of the disease is speculative. Nevertheless, it is well-established that a chronic and untreated state of anxiety is related to significant disability and, as a consequence, to poorer quality of life [45]. …”
Section: Resultsmentioning
confidence: 99%
“…Patients diagnosed with BD-II were most likely to present initially in depression (77.5%), and in BD-I cases, there was also prominent initial depression (46.4%) as well as psychosis or mania (13.3-22.4%; Table 1). It may also be significant that the latency from onset of BD to systematic diagnostic assessment and enrollment in regular and sustained treatment at the study centers was nearly 3 years longer among patients diagnosed BD-II than BD-I, and 11 years overall; this delay may reflect the severity of mania among BD-I cases requiring early intervention as well as delay in differentiating BD-II from recurrent depression (31)(32)(33)(34). It is also noteworthy that overall morbidity differed only moderately by onset type, with high values following hypomania and low values after initial anxiety (Table 3, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Zbog toga ne čudi da je dijagnostikovanje bipolarnog poremećaja, kao oboljenja sa više faza (manična, depresivna, mešovita) i aspecifičnim početkom (najčešće depresivna epizoda) otežano te dovodi do odlaganja adekvatnog terapijskog tretmana (stabilizator raspoloženja), produženja perioda nelečenosti i posledično lošijeg ishoda, ali i teže klasifikacije stadijuma razvoja [9,10,13,14,15].…”
Section: Bipolarni Spektar -Kontinualni Pristup Sagledavanju Bipolarnunclassified